2019
DOI: 10.1038/s41563-019-0439-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of electrochemical dissolution of metals in porous media

Abstract: Metals embedded in porous media interact electrochemically with the liquid phase contained in the pores. A widespread form of this, adversely affecting the integrity of engineered structures, is corrosion of steel in porous media or in natural environments. While it is well-documented that the rate of this electrochemical dissolution process can vary over several orders of magnitude, understanding the underlying mechanisms remains a critical challenge hampering the development of reliable predictive models. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…Concerning this capacitance (C dl ), Table 3 also shows an increase between the beginning of the tests (phase 1) and the last phases (4 and 5) by a factor of 3, which may again be related to a higher effective steel surface area due to surface roughening. This hypothesis is in agreement with earlier studies showing that corrosion of metals embedded in porous media (here, a porous corrosion product layer) is at the microscopic scale non-uniform and thus leads to surface roughening (Romanoff 1957;Stefanoni et al 2019). Thus, in summary, the increase in corrosion rate by a factor of 3 between phase 1 (approx.…”
Section: Metal Surface Changes (Roughening Scale Formation)supporting
confidence: 92%
“…Concerning this capacitance (C dl ), Table 3 also shows an increase between the beginning of the tests (phase 1) and the last phases (4 and 5) by a factor of 3, which may again be related to a higher effective steel surface area due to surface roughening. This hypothesis is in agreement with earlier studies showing that corrosion of metals embedded in porous media (here, a porous corrosion product layer) is at the microscopic scale non-uniform and thus leads to surface roughening (Romanoff 1957;Stefanoni et al 2019). Thus, in summary, the increase in corrosion rate by a factor of 3 between phase 1 (approx.…”
Section: Metal Surface Changes (Roughening Scale Formation)supporting
confidence: 92%
“…Another effect promoting depassivation at pH values around 8-9 may be the formation of small galvanic cells. This is supported by the view that corrosion of metals in meso-tomacro-porous media is a non-uniform process at the microscopic scale [37]. The complexity of the steel-concrete interface [38] gives rise to local heterogeneities in water presence at the steel surface, and may thus promote local differences in pH and oxygenation (similar to the "Evans drop" [39]).…”
Section: Mechanisms Depassivation and Initiation Of Corrosion In Carbmentioning
confidence: 99%
“…A number of studies showed that the instantaneous corrosion rate in carbonated concrete increases exponentially with the relative humidity in the concrete [42][43][44][45][46]. This relationship was recently explained by the dual role of the pore structure of the cementitious medium surrounding the embedded steel [37]. First, the pore structure governs the amount of water that is held in the pore system when in equilibrium with a given exposure moisture condition.…”
Section: Corrosion Rate 421 Fundamental Processes Controlling the Cmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower average volume loss of 2.5% was found also for 2550-S3, apart from the bottom part of the bar where a localized volume loss up to 9% was observed. Recently, Stefanoni et al [23] observed that the more porous the medium around the steel reinforcement, the more aggressive corrosion occurs due to the dual role of the pore structure (in terms of transport limitations and inhomogeneity of the interfacial zone). Since blended cements lead to a denser microstructure than that of OPC, it is not surprising that, on average, rebars embedded in OPC-based cores had the highest volume loss.…”
Section: On the Influence Of Concrete Properties On Corrosion Behaviormentioning
confidence: 99%